Reflecting Culturally Responsive and Communicative Teaching (CRCT) through Partnership Commitment - Zainal Berlian; Miftachul Huda (MDPI AG, 2022)
The strategic approach to enhance cultural skills is aligned with social feeling and sense of belonging as an important element to underlie the interaction pathway with others' diverse backgrounds. Such an approach of teaching model could be transformed and prepared to encourage ability to communicate and relate to others from diverse backgrounds. The following phase of sufficient integration amongst cognitive, social and emotional substance is reflect in the culturally responsive and communicative teaching (CRCT). This mode is an important element to advance the diverse students amidst an increasingly complex and pluralistic society. This paper is aimed at examining CRCT by having a critical look into the partnership commitment amongst interracial teachers' daily school interaction. Data collection was conducted with 10 interracial teachers with a focus on the approach of how their partnership commitment is reflected and practiced in their daily school interaction. Thematic analysis was employed to obtain the main points of data to give insight into the multicultural school society. The findings reveal that an understanding of CRCT articulated into partnership engagement commitment has a core of three main points. These are: expanding self-awareness on cultural identity; enhancing culturally mediated emotion of social situations; and developing instructional practice for cultural sensitivity. The implication for students' experiential learning in the multicultural classroom was also discussed. The contribution of this paper can be exerted among those involved in the education sectors. These include students, educators, principals, learning facilitators, researchers, educational technologist, instructional designers and practitioners. This is also included among the researchers who are interested in exploring, understanding and developing discerning perspectives on diversity and diverse learners in 21st century education. This study is expected to contribute by giving solving skills with the strategic approach articulated into a particular guideline to give a clear understanding in responding the multicultural classroom in the interracial school society context. This study is considered to elaborate the good feedback on the importance of CRCT in responding to emerging trends on the facades of diversity among diverse learners.